Analysis of Uncontrolled Rectifier with Different Passive Filters: A Comparative Evaluation of Passive Filters for Distortion Reduction in Uncontrolled Rectifiers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Power electronics, which is a rapidly growing area in terms of research and applications, uses modern electronics technology to convert electric power from one form to another. The ‘current’ drawn by these devices is distorted so there is a need for filters to reduce the distortion. In this paper a comparative evaluation of different types of passive filters used to reduce the distortion and improve the power factor in AC–DC converter. Performance improvement is shown using simulation software.